7. WATER QUALITY STATUS AT THE COMMON SUPPLY STATIONS AND PLANTS IN HAU GIANG PROVINCE IN 2022 AND AFFECTING FACTORS (Vietnam Journal of Community Medicine, 2023)
Objective: To describe the water quality situation at supply units and analyze some factors affecting water quality in Hau Giang province in 2023. Subject and method: A cross-sectional descriptive study, combining quantitative and qualitative, was conducted on 60 water supply units in Hau Giang province in 2022 to assess the situation and some factors affecting water quality. They were collecting secondary data based on test results of water samples from water supply units by the Provincial Center for Disease Control and interviewing 60 managers with a questionnaire according to Circular No. 50/2015/TT-BYT. Results: The results show that the water supply units with water samples reached 13/13 criteria according to QCVN 01-01:2018/BYT, accounting for 43.3%. Some factors affecting water quality include the professional training level of managers (OR=10.41; 95%CI: 1.24-87.7); water supply model (OR=8.81; 95%CI: 2.66-29.15); water quality self-control (OR=1.7; 95%CI: 1.55-2.00); risk of polluted water source (OR=3.33; 95%CI: 1.06-10.27); operating time of the units (OR=6.45; 95%CI: 1.55-26.83); water treatment and disinfection (OR=1.36; 95%CI: 1.31-1.42). Conclusion: Units with water samples meeting the criteria according to QCVN 01-01:2018/BYT accounted for the average rate. Some factors affecting water quality include the professional training level of managers, water supply model, self-control of water quality, risk of polluted water source, operation time of units, water treatment and disinfection.
Keywords: Water supply units; water quality; QCVN 01-01:2018/BYT.